Role of Fungi in Biodegradation of Bisphenol A: A Review - Kristanti, Risky Ayu; Ningsih, Fitria; Yati, Indri; Kasongo, Joseph; Mtui, Elias; Rachana, Kong (Tropical Aquatic and Soil Pollution, 2023)
Bisphenol A (BPA) is recognized as an endocrine disruptor, capable of interfering with the normal functioning of hormones within the body by mimicking the effects of estrogen. Drinking water is one of the most common pathways of exposure to BPA as it can permeate plastic products and other materials, entering water sources. This article presents a comprehensive overview of BPA, including its incidence, origins, environmental fate, its impact on human health, and the role of fungi in the biodegradation of BPA. Fungi are natural decomposers, capable of breaking down organic compounds, including BPA, under suitable conditions. Studies have demonstrated that specific species of fungi can effectively biodegrade BPA. Some fungi utilize ligninolytic enzymes, such as laccases and peroxidases, to break down the phenolic rings of BPA. Other fungi employ non-ligninolytic enzymes, such as esterases and hydrolases, to cleave the ester linkages in BPA. Furthermore, some fungi can break down BPA via cometabolic pathways, whereby the chemical is degraded as a side reaction to the degradation of another substrate. The use of immobilized enzymes for BPA degradation has also demonstrated potential. Immobilized enzymes are those that are attached to a solid support, such as a polymer or matrix, allowing them to be used multiple times and enhance their stability and catalytic activity